2019
DOI: 10.1111/are.14364
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of dietary apple cider vinegar as an organic acidifier on the growth performance, digestive enzymes and mucosal immunity of green terror (Andinoacara rivulatus)

Abstract: The present study was designed to investigate the effects of dietary apple cider vinegar (ACV) on digestive enzyme activity and growth performance as well as immune responses and antibacterial activity of skin mucus in green terror (Andinoacara rivulatus). Fish were fed diets supplemented with 0%, 1%, 2% and 4% of ACV (40.830 ppm acetic acid concentration) for 63 days. The final weight and weight gain values were observed to be significantly higher in fish fed with 2% of ACV compared to the control group (p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Organic acids or their salts with different origins including internal (by microbiota activity) or external (via along inclusion in diet) are regarded as non‐antibiotic growth promoters (Lückstädt, 2008; da Silva et al., 2016). Similar to the symbiotic effects on biological indices of aquatic species, organic acids act through the modification of gastrointestinal microbiota (Ahmadniaye Motlagh et al., 2019; De Schryver et al., 2010; Defoirdt et al., 2011; Lückstädt, 2008; Mine & Boopathy, 2011), the proliferation of gut epithelial cell (Ng & Koh, 2017), the action of digestive enzymes (Ahmadniaye Motlagh et al., 2019; da Silva et al., 2016), the improvement of nutrition efficiency indices (Sarker et al., 2012a, 2012b), lipid synthesis (Marcil et al., 2002) and bioenergetic pathways such as the routes of citric and carboxylic acids (Lückstädt, 2008; Ng & Koh, 2017). In this regard, feeding behaviour of aquatics can affect the process of diet formulation and select aquafeed production technology (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organic acids or their salts with different origins including internal (by microbiota activity) or external (via along inclusion in diet) are regarded as non‐antibiotic growth promoters (Lückstädt, 2008; da Silva et al., 2016). Similar to the symbiotic effects on biological indices of aquatic species, organic acids act through the modification of gastrointestinal microbiota (Ahmadniaye Motlagh et al., 2019; De Schryver et al., 2010; Defoirdt et al., 2011; Lückstädt, 2008; Mine & Boopathy, 2011), the proliferation of gut epithelial cell (Ng & Koh, 2017), the action of digestive enzymes (Ahmadniaye Motlagh et al., 2019; da Silva et al., 2016), the improvement of nutrition efficiency indices (Sarker et al., 2012a, 2012b), lipid synthesis (Marcil et al., 2002) and bioenergetic pathways such as the routes of citric and carboxylic acids (Lückstädt, 2008; Ng & Koh, 2017). In this regard, feeding behaviour of aquatics can affect the process of diet formulation and select aquafeed production technology (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no sufficient evidence about the specific effect of organic acids on the activities of digestive enzymes (e.g. alkaline protease, lipase and amylase), but some researchers believed that organic acids penetrate the Gram‐negative bacteria cell wall, free protons, diminish the intracellular pH of bacterial cytoplasm and, finally, cause cell death (Ahmadniaye Motlagh et al., 2019; Lückstädt, 2008; da Silva et al., 2013). In this regard, the growth inhibition of Vibrio cambelli exposed to different organic acids (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, mucus plays a role in entrapment of pathogens by using immune parameters such as lectins, proteolytic enzymes, pentraxins, lysozyme, complement proteins, antibacterial peptides and immunoglobulins. It has been well documented that several fish species have immune parameters in their epidermal mucus that play a crucial role in their immune responses (Ahmadniaye Motlagh et al., 2020; Dawood et al., 2017; Roosta et al., 2014). It also has been found that the antibacterial activity of fish skin mucus could be affected by factors such as the physiological conditions of the fish and their growth and maturity (Dang et al., 2020; Subramanian et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been said that alkaline phosphatase, during wound healing and parasite infection or stress, acts as a pathogen due to its hydrolytic activity, which has a protective function at the beginning (Ahmadniaye Motlagh et al., 2020; Mohammadi, Rashidian, Hoseinifar, Naserabad, & Doan, 2020). The ALP activity in mucosa of fish fed with 4% and 6% ML was significantly higher than the activity level achieved with the 2% dose of ML.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation